Unilateral floppy eyelid syndrome with ipsilateral intolerance to brimonidine - Leidiane Adriano Pereira; Sidney Julio Faria-e-Sousa; Gleiton Carlos Mendonça; Jailton Vieira Silva; Amanda Alexia Rodrigues Vieira (Revista Brasileira de Oftalmologia)
Abstract The authors report a case of unilateral floppy eyelid syndrome with ipsilateral intolerance to brimonidine in a 65-year-old man. The singularity of this case is the combination of two rare illnesses of great phlogistic potentiality in the same eye. The purpose of this article is to report a case of unilateral floppy eyelid syndrome with ipsilateral intolerance to brimonidine, emphasizing a possible relation between them. The result was a unilateral keratopathy that emulated an intraepithelial neoplasia. The key to solving the problem was an unexplained anterior uveitis that raised the suspicion of drug toxicity.The upper eyelid eversion of the affected eye during sleep seemed to be the common denominator of both ailments. The bizarre aspect of the epitheliopathy most likely resulted from the combination of trauma, insufficient lubrication, and drug intolerance.